Analysis of the Management of School Operational Assistance (BOS) funds to improve educational performance at SD Negeri Inpres Dok IX Jayapura City - Helena Gracelia U. Gobay; Halomoan Hutajulu; Elsyan R. Marlissa (Goodwood Publishing, 2025)
Purpose: This study aims to analyze the management of School Operational Assistance (BOS) funds in improving educational performance at SD Negeri Inpres Dok IX, Jayapura City. The research focuses on the fund management process, supporting and inhibiting factors, and its impact on school performance. Methodology: A descriptive qualitative approach with a case study design was applied. Data were collected through questionnaires, interviews, and observations involving principals, teachers, students, BOS team members, parents, and Education Office representatives. Data were analyzed using descriptive techniques and interpreted through average Likert-scale scores. Results: The findings indicate that BOS funds were managed transparently, efficiently, and accountably, mainly allocated for teacher salaries, facility maintenance, and learning activities. Supporting factors included stakeholder participation and solid administrative documentation, while inhibiting factors involved limited financial management training and low budget allocation for teacher development. SWOT analysis showed that although BOS funds improved facilities and student outcomes, human resource capacity remained a weakness. Conclusions: Effective BOS fund management has significantly enhanced educational performance through improved learning facilities and activities. Sustainable progress requires continuous investment in teacher training and stronger financial management skills. Limitations: The study’s scope was limited to one school and a specific period, thus limiting broader generalization. Contribution: This research contributes to educational finance studies by highlighting how transparent BOS fund management drives performance improvement and offers practical insights for schools in similar socio-economic contexts.